2015
DOI: 10.1002/mc.22364
|View full text |Cite
|
Sign up to set email alerts
|

The garlic compound ajoene targets protein folding in the endoplasmic reticulum of cancer cells

Abstract: Ajoene is a natural allylsulfur compound found in crushed garlic that arrests growth and induces apoptosis in cancer cells. To gain mechanistic insights into the cytotoxicity of ajoene in cancer cells, two fluorescently labelled ajoene analogs with dansyl- (DP) and fluorescein- (FOX) tags were synthesized. The tagged ajoenes were found to retain their activity at inhibiting proliferation and inducing apoptosis in MDA-MB-231 human breast-cancer and WHCO1 human esophageal-cancer cells. Both tagged ajoenes locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 68 publications
3
57
0
Order By: Relevance
“…Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016). The hypothesis underlying these studies may partially be explained by the anti-mutagenic and immune-modulatory effects of garlic derived allylsulfur compounds and their ability to exert a direct anti-proliferative effect on growing tumour cells by inducing apoptosis Powolny and Singh, 2008;Schafer and Kaschula, 2014).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016). The hypothesis underlying these studies may partially be explained by the anti-mutagenic and immune-modulatory effects of garlic derived allylsulfur compounds and their ability to exert a direct anti-proliferative effect on growing tumour cells by inducing apoptosis Powolny and Singh, 2008;Schafer and Kaschula, 2014).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…Garlic‐derived organosulfur compounds, including diallyl sulfide (DAS), diallyl disulfide (DADS), and diallyl trisulfide (DATS), are HDAC inhibitors with anticarcinogenic properties . In particular, DADS and DATS can modulate numerous biological mechanisms that may influence carcinogenesis in non‐tumor colon, glioblastoma, stomach cancer, and others . We have reported that DADS was a promising cancer chemopreventive agent for a skin carcinogenic model through p21‐dependent Nrf2 stabilization .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In particular, DADS and DATS can modulate numerous biological mechanisms that may influence carcinogenesis in non-tumor colon, glioblastoma, stomach cancer, and others. [22][23][24][25] We have reported that DADS was a promising cancer chemopreventive agent for a skin carcinogenic model through p21dependent Nrf2 stabilization. 26 DATS inhibited MMP2/9 activity and the metastasis of breast cancer cells in vitro, as a potential anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…Anke Wilhelm (University of the Free State) divulged her recent results in HPLC‐based activity profiling in a zebrafish locomotive assay for the identification of GABA A receptor modulators (Figure ) . Dr. Catherine Kaschula gave us an update on her ongoing studies into the cancer preventative properties of ajoene and related garlic analogues as well as the biological activity of their synthetic analogies and the potential biological targets of these compounds …”
Section: Natural Product Chemistrymentioning
confidence: 99%